Physics Learning E-Module Integrated with Practicing Pancasila Values on Momentum and Impulse: Is it Effective to Improve Students’ Critical Thinking Skill and Hard Work Character? - Nur Arviyanto Himawan; Ariswan Ariswan (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
The use of independent instructional materials and the integration of Pancasila values need to improve students’ cognitive and affective abilities. This study aims to determine the effectiveness of the integrated physics learning e-module integrated with practicing Pancasila values in momentum and impulse to improve students’ critical thinking skills and hard work character. The independent variable is the use of integrated physics learning e-module integrated with practicing Pancasila values and textbook, while the dependent variable is the critical thinking skill and hard work character. The type of this research is Quasi Experiment with a Pretest-Posttest Control-Group Design. The sampling technique used was cluster random sampling involving 70 students of the 10th-grade science class of a State Islamic High School in Yogyakarta. The instruments used were essay questions of critical thinking skills and a hard work character questionnaire. The data were then analyzed using MANOVA statistical test. The results showed that the physics learning e-module integrated with practicing Pancasila values in momentum and impulse effectively improved the students’ critical thinking skills and hard work character on momentum and impulse. This shows that the use of independent instructional material such as e-modules has a good impact on improving cognitive and affective abilities, not only because students learn content in e-modules, but also because they can monitor their learning process, realize their mistakes, and plan the learning process according to their abilities.